Algunos símbolos en el mito del origen del mundo en Oxkintok - Rivera Dorado, Miguel (Revista Española de Antropología Americana, 2003)
From 1985 until 1991 the team of the Misión Arqueológica de España en México was the guest of the small town of Maxcanú (Yucatán), while working in the maya ruins of Oxkintok. One mith colected in this time is here analised and argumented on the ground of literary simbolism.